Finance and Development, December 1974. (Finance and Development; Finance and Development ;, 1974)
This paper presents main highlights of the IMF Meetings in 1974. Four dominant themes for the annual discussion were clearly stated by Mr. John N. Turner, Governor of the IMF and Bank for Canada. These were inflation, reduced economic growth rates, payments disequilibria, and the crisis situation in many developing countries. There was broad agreement with the opinion of Mr. Yong Hwan Kim, Governor of the IMF and Bank for Korea, that one of the most serious problems facing the world today is inflation.